Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $x^{(k)}$ and $b$ be vectors and $L,\ D, \ U$ be lower, diagonal, upper triangular matrices.

We have:

$x^{(k)}=(I+D^{-1}L)^{-1}(D^{-1}b-D^{-1}Ux^{(k-1)})$ (1)

How does the following follow from (1):

$x^{(k)}=-(D+L)^{-1}Ux^{(k-1)}+(D+L)^{-1}b$

share|improve this question
1  
Remember that $(AB)^{-1} = B^{-1}*A^{-1}$ and use this on $A = D$ and $B = I + D^{-1}L$ –  Cocopuffs Aug 18 '12 at 17:19
    
Perfect, thank you! –  Chris Aug 18 '12 at 20:55

1 Answer 1

With Cocopuffs input:

$(I+D^{-1}L)^{-1}(D^{-1}b-D^{-1}Ux^{(k-1)})=(I+D^{-1}L)^{-1}D^{-1}(b-Ux^{(k-1)})=(D(I+D^{-1}L))^{-1}(b-Ux^{(k-1)})=-(D+L)^{-1}Ux^{(k-1)}+(D+L)^{-1}b$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.